2020
DOI: 10.1128/mra.01291-19
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequences of Two NDM-1-Producing Pseudomonas aeruginosa Strains Isolated in a Clinical Setting in Albania in 2018

Abstract: Isolation of metallo-β-lactamase-producing, carbapenem-resistant, Pseudomonas aeruginosa strains is increasingly being documented worldwide; their presence constitutes a public health threat. Here, we report draft genome sequences of two New Delhi metallo-β-lactamase-1-producing, multidrug-resistant, P. aeruginosa strains of sequence type 235 that were isolated from the surgical wound of two patients hospitalized in the same ward.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…It should be mentioned that this is the second study form the Balkans that utilizes ONT long reads (MinION) in combination with the short reads generated by an Illumina platform (Illumina HiSeq, 2 × 150 bp) [ 131 ]. This results in the generation of the second complete genome of a CRPA isolate again carrying the bla NDM-1 gene similar to the report from Bulgaria [ 127 ]. The absence of essential clinical information regarding the isolates that were subject to WGS can be considered as the biggest limitation of this study.…”
Section: P Aeruginosasupporting
confidence: 73%
See 2 more Smart Citations
“…It should be mentioned that this is the second study form the Balkans that utilizes ONT long reads (MinION) in combination with the short reads generated by an Illumina platform (Illumina HiSeq, 2 × 150 bp) [ 131 ]. This results in the generation of the second complete genome of a CRPA isolate again carrying the bla NDM-1 gene similar to the report from Bulgaria [ 127 ]. The absence of essential clinical information regarding the isolates that were subject to WGS can be considered as the biggest limitation of this study.…”
Section: P Aeruginosasupporting
confidence: 73%
“…In their study, Tafaj et al report the genome sequences of two NDM-1-producing P. aeruginosa strains of ST235 that were isolated from the surgical wound of two inpatients in Tirana [ 127 ]. The WGS procedure was carried out at the San Raffaele Hospital (Milan, Italy) using Illumina NextSeq 500 (2 × 150 bp) sequencing.…”
Section: P Aeruginosamentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies also supported that a longer hospital stay increases the risk of AB infection. [ 23 , 24 ] We found that the absence of coinfection to be an additional risk factor. Consistent with our results, the coinfection of other bacteria was rare in AB-infected patients.…”
Section: Discussionmentioning
confidence: 85%
“…Since the first discovery of NDM-1-producing P. aeruginosa from Serbia in 2011 [8], it has been isolated mostly in Asia, Europe, and Africa [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] (Table 1). ST235 was the only sequence type identified in all previously isolated NDM-1-producing P. aeruginosa strains.…”
Section: Discussionmentioning
confidence: 99%